Proposal for a 6‐step approach for differential diagnosis of neonatal erythroderma. (15th March 2022) - Cuperus, E.; Bygum, A.; Boeckmann, L.; Bodemer, C.; Bolling, M.C.; Caproni, M.; Diociaiuti, A.; Emmert, S.; Fischer, J.; Gostynski, A.; Guez, S.; van Gijn, M.E.; et al.
Abstract: The broad differential diagnosis of neonatal erythroderma often poses a diagnostic challenge. Mortality of neonatal erythroderma is high due to complications of the erythroderma itself and the occasionally severe and life‐threatening underlying disease. Early correct recognition of the underlying cause leads to better treatment and prognosis. Currently, neonatal erythroderma is approached on a case‐by‐case basis. The purpose of this scoping review was to develop a diagnostic approach in neonatal erythroderma. After a systematic literature search in Embase (January 1990 – May 2020, 74 cases of neonatal erythroderma were identified, and 50+ diagnoses could be extracted. Main causes were the ichthyoses (40%) and primary immunodeficiencies (35%). Congenital erythroderma was present in 64% (47/74) of the cases, predominantly with congenital ichthyosis (11/11; 100%), Netherton syndrome (12/14, 86%) and Omenn syndrome (11/23, 48%). Time until diagnosis ranged from 102 days to 116 days for cases of non‐congenital erythroderma and congenital erythroderma respectively. Among the 74 identified cases a total of 17 patients (23%) died within a mean of 158 days and were related to Omenn syndrome (35%), graft‐versus‐host disease (67%) and Netherton syndrome (18%). Disease history and physical examination are summarized in this paper. Age of onset and a collodion membrane can help to narrow the differential diagnoses. Investigations of blood, histology, hair analysis, genetic analysis and clinical imaging are summarized and discussed. A standard blood investigation is proposed, and the need for skin biopsies with lympho‐epithelial Kazal‐type related Inhibitor staining is highlighted. Overall, this review shows that diagnostic procedures narrow the differential diagnosis in neonatal erythroderma. A 6‐step flowchart for the diagnostic approach for neonatal erythroderma during the first month of life is proposed. The approach was made with the support of expert leaders from international multidisciplinary collaborations in the European Reference Network Skin‐subthematic group Ichthyosis.